Length of Stay of Orthopaedic Inpatients at a Teaching Hospital in Eastern Part of Nepal - Bibhuti Nath Mishra (Journal of Nepal Medical Association, 2015)
Introduction: This study aimed to analyze the average length of stay of all inpatients in the department of Orthopaedics and to compare the variations in hospital stay between age, gender, traumatic and non-traumatic co-morbidities and modality of payment.